Penerapan Modal Sosial, Dinamika Gender, dan Keberlanjutan Usaha Pisang Cavendish dan Kopi di KWT Bener Meriah. - Mursyidin Mursyidin; Nur Hafni; Ainol Mardhiah; Rayuwati Rayuwati; Dedy Darmansyah; Agung Rivandi; Lukman Maulana; Huzaifah Huzaifah; Aldi Prayogi (Universitas Teuku Umar, 2024)
Economic development in rural Indonesia heavily relies on the agricultural sector, including the production of bananas and coffee. Bener Meriah Regency is one of the key production centers in this sector. The success of agricultural enterprises is not only determined by economic and technical factors but also by social capital, which includes social networks, trust, and community norms. This study examines the interaction between gender dynamics and social capital in the context of banana and coffee enterprises in KWT Karya Maju, Bener Meriah Regency. Gender inequality often hinders women's access to social capital on an equal footing with men, affecting the sustainability of the enterprise. This research adopts a qualitative approach through in-depth interviews, observations, and document analysis. The findings reveal that men have broader access to influential social networks, while women are often restricted by social norms and smaller local networks. This inequality impacts production efficiency and market opportunities. Gender-sensitive interventions are needed to expand women's social networks and enhance their participation in decision-making processes. The study concludes that the sustainability of enterprises depends on both social capital and gender equality in its utilization.